Challenges and opportunities to advance manufacturing research for sustainable battery life cycles - Johansson, Björn; Despeisse, Mélanie; Bokrantz, Jon; Braun, Greta; Cao, Huizhong; Chari, Arpita; Fang, Qi; González Chávez, Clarissa A.; Skoogh, Anders; Söderlund, Henrik; Wang, Hao; Wärmefjord, Kristina; et al. (Frontiers in Manufacturing Technology, 2024)
Advanced manufacturing research for sustainable battery life cycles is of utmost importance to reach net zero carbon emissions (European Commission, 2023b) as well as several of the United Nations Sustainable Development Goals (UNSDGs), for example: 30% reduction of CO2 emission, 10 million job opportunities and access to electricity for 600 million people (World Economic Forum, 2019). This editorial paper highlights international motivations for pursuing more sustainable manufacturing practices and discusses key research topics in battery manufacturing. Batteries will be central to our sustainable future as generation and storage become key components to on-demand energy supply. Four underlying themes are identified to address industrial needs in this field:1. Digitalizing and automating production capabilities: data-driven solutions for production quality, smart maintenance, automation, and human factors, 2. Human-centric production: extended reality for operator support and skills development, 3. Circular battery life cycles: circular battery systems supported by service-based and other novel business models, 4. Future topics for battery value chains: increased industrial resilience and transparency with digital product passports, and next-generation battery chemistries.Challenges and opportunities along these themes are highlighted for transforming battery value chains through circularity and more sustainable production, with a particular emphasis on lithium-ion batteries (LIB). The paper concludes with directions for further research to advance a circular and sustainable battery value chain through utilizing the full potential of digitalization realising a cleaner, more energy-efficient society.